Kryzys ekonomiczny w Uruk w ostatnich latach rządów asyryjskich w świete tzw. archiwum Nabu-uszallima - Zawadski, Stefan
The Economie Crisis in Uruk during the Last Years of Assyrian Rule in the Light of the So-Called Nabû-ušallim’s Archives; English summary 152.